Anger and Strategic Behavior: A Level-k Analysis - Alessandro Castagnetti; Eugenio Proto (Institute of Labor Economics (IZA), 2020)
Anger is an important driver in shaping economic activities, particularly in instances that involve strategic interactions between individuals. Here we test whether anger impairs the capacity to think strategically, and we analyze the implications of our result on bargaining and cooperation games. Accordingly, with a preregistered experiment (Experiment 1), we externally induce anger to a subgroup of subjects following a standard procedure that we verify by using a novel method of text analysis. We show that anger can impair the capacity to think strategically in a beauty contest game. Angry subjects choose numbers further away from the Nash equilibrium, and earn significantly lower profits. A structural analysis estimates that there is an increase in the share of level-zero players in the treated group compared to the control group. Furthermore, with a second preregistered experiment (Experiment 2), we show that this effect is not common to all negative emotions. Sad subjects do not play significantly further away from the Nash equilibrium than the control group in the same beauty contest game of Experiment 1, and sadness does not lead to more level-zero play.
Keywords: C92; D90; D91; 330; anger; induced emotions; strategic interactions; beauty-contest